PERAN PEMERINTAH DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR DALAM PENGEMBANGAN DESA WISATA TAHUN 2020-2021 - Muhammad Al Kadri; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Village autonomy is genuine, unanimous and complete autonomy and is not a gift from the government. An independent village is an advanced village that has the ability to carry out village development to improve the quality of life and life as much as possible for welfare. The Village Government in the development of a tourist village is all the activities and efforts made to attract tourists, with an effort to provide tourism support facilities that aim to meet the needs of visiting tourists. This study aims to determine the development of the Koto Mesjid tourist village, XIII District of Koto Kampar by the Village Government in 2021. Then to determine the inhibiting factors in the development of the Koto Mesjid tourist village, XIII Koto Kampar District by the Village government in 2021. The research method used is a qualitative method by explaining the data descriptively. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. The informants in this study were village heads, BPD heads, heads of government, POKDARWIS, heads of Riau LPPM STP, Kampar Regency Culture and Tourism Office. The results of the research are that the role of the government of Koto Mesjid Village in the development of a tourist village in 2020-2021 has not gone well. The implementation of the development of a tourist village is based on Law Number 6 of 2014 concerning Villages and District Head Decree Number: Kpts/UPK-Destination/47 concerning the establishment of a Tourism Village in 2019. The Koto Mesjid Village Government in developing a tourism village is still not optimal in terms of infrastructure development, promotion, budget, utilization of natural resources and development of human resources. Keywords: Tourism Village SDM Development, Tourism Village Partnership, Tourism Village Promotion